Therapeutic potential of ozonized sunflower oil in skin tissue repair - Cueto, Thalia Malave (2025)
The skin plays a crucial role in protecting the body from external agents and injuries. When damaged, it goes through a process of acute inflammatory response, followed by the tissue repair phase. However, some injuries can present difficulties during the healing process. In view of this, studies have investigated substances with therapeutic potential, such as ozonated oils, which demonstrate antimicrobial, anti- inflammatory and regenerative properties. They stand out as promising alternatives for accelerating skin repair, offering effective solutions to damage to the integrity of the skin. This integrative review investigated the role of ozonized sunflower oil in tissue repair by searching the PubMed, Scopus, Embase and Web of Science databases without time restrictions using the keywords sunflower oil, ozonized sunflower oil, tissue repair and wound healing. Inclusion criteria included in vivo and in vitro studies, controlled trials and availability of full text. The selection process followed the PRISMA guidelines. Of the 918 studies retrieved, 14 met the inclusion criteria. The ozonized sunflower oil has been shown to improve wound healing by reducing inflammation, stimulating fibroblast proliferation and promoting collagen remodeling. Studies in animal models have shown that ozonated sunflower oil accelerates wound closure and reduces bacterial infections, highlighting its potential as a promising therapeutic alternative for wound healing due to its antimicrobial and anti-inflammatory effects. However, future clinical trials are needed to validate its efficacy and safety in human applications, as well as to establish standardized treatment protocols.